Crystallization Pathway for Crystallization of FeB Nanoparticles - Kien, Pham Huu; Mai An, Pham; Hong Linh, Nguyen; Thuy Trang, Giap (VNU Journal of Science: Mathematics - Physics; Vol 35 No 3DO - 10.25073/2588-1124/vnumap.4346, 2019)
In this study, the FeB nanoparticle (NP) consisting of 5,000 particles (4,500 Fe atoms and 500 B atoms) was investigated by means of molecular dynamics (MD) simulation. When the amorphous FeB nanoparticle is annealed at the temperature of 900 K for a long time, it is crystallized into a bcc crystalline structure. The simulation shows that the sample undergoes crystallization via the nucleation mechanism. During the crystallization, B atoms diffuse to the boundary region of Fe crystal. The crystal growth proceeds when this boundary region attains specific properties which are defined by the fraction of B atoms and the energies of AB-atoms and CB-atoms. The study further indicates that the crystalline and mixed FeB nanoparticle consists of three distinct parts including Fe crystalline and two FeB amorphous parts (B-poor and B-rich amorphous parts). The different polymorphs of FeB nanoparticle differ in the local structure, size of Fe crystal and energies of different type atoms.